Alice 3 cookbook : 79 recipes to harness the power of Alice 3 for teaching students to build attractive and interactive 3D scenes and videos /: 79 recipes to harness the power of Alice 3 for teaching students to build attractive and interactive 3D scenes and videos. (2011) - Unknown
No abstract available